Konstruowanie narracyjnej tożsamości religijnej dziecka w koncepcji Sofii Cavalletti elementem edukacji inkluzyjnej - Surma, Barbara (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Changing interpretive concept of man, which assumes the subjectivity of the individual, his continuous change in becoming the person and activity in the construction of his own development, relationships with others and changing world also sets new directions of changes in modern education, including religious. The basis of subjectivity, and also the aim of education is the development of man as a person, together with his free „self”. Self-determination, identity formation of own „self” takes place in cooperation with the reality that man himself codetermines and at the same time he affects it secondarily. Giving meaning of „self” determines the future of peoples’ operations. Understanding yourself and the world is the result of the adoption of two certainties: the existence of speaking for the group with which one is identified and existence of individual point of view of these statements. The exemplification of the category of narrative and constructivism in religious education, which may be proposed as an inclusive education, is an Italian concept of Sofia Cavalletti. Some chosen assumptions of this concept are examined above.
Keywords: constructivism; inclusion; narrative religious education; pedagogy of Maria Montessori; religious education concept of Sofia Cavalletti